2011
DOI: 10.1007/s11096-011-9559-1
|View full text |Cite
|
Sign up to set email alerts
|

The appropriateness of enoxaparin use in Lebanese hospitals: a quality evaluation study

Abstract: This study highlighted the improper practice and thus the need of implementation of clinical practice guidelines for the dosing of enoxaparin, in Lebanese hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…14 Similar to in-hospital studies, rates of regimen compliance are higher in thrombosis prophylaxis than in curative indications. 14,15 However, the interpretation of regimen compliance should be cautious in patients with therapeutic indication, since dosages could have been adapted after results of biological monitoring (activated partial thromboplastin time for UHs or anti-Xa activity for LWMHs). Also, we chose a stringent range for compliance with dose (±0.05 mL, based on clinicians’ experience).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Similar to in-hospital studies, rates of regimen compliance are higher in thrombosis prophylaxis than in curative indications. 14,15 However, the interpretation of regimen compliance should be cautious in patients with therapeutic indication, since dosages could have been adapted after results of biological monitoring (activated partial thromboplastin time for UHs or anti-Xa activity for LWMHs). Also, we chose a stringent range for compliance with dose (±0.05 mL, based on clinicians’ experience).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of adverse events related to parenteral anticoagulants therapy (5.4%) is also in range with previous studies (3.7%-5%). 14,15 Bleedings (0.6% of patients) remain the most frequent serious adverse events related to parenteral anticoagulants therapy. However, our sample size was insufficient to assess the association between compliance with SPCs/guidelines and adverse events related to parenteral anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study that evaluated the appropriateness of enoxaparin use, it was reported that 40% of the 463 study participants from Lebanese hospitals received improper enoxaparin dosing [10][11][12][13][14][15]. This was mostly observed in the VTE prophylaxis group.…”
Section: Introductionmentioning
confidence: 99%